2017
DOI: 10.1007/s13644-017-0287-4
|View full text |Cite
|
Sign up to set email alerts
|

“Leaving the Faith of Our Fathers”: Intergenerational Persistence and Class Cleavage of Evangelicals in Chile

Abstract: Several studies have consistently linked the Evangelical breakdown in Latin America as a mass movement mainly adopted by impoverished working class individuals. However, little is known about how religious inheritance and recruitment of Evangelical movements is affected when status conditions improve along individuals trajectories. Using Bicentenario Survey from 2006 to 2010 we analyze how intergenerational patterns of religious persistence in Chile relate to individuals’ educational attainment and intergenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In Chile, Christian spirituality is strong, because most of the population identifies with Catholic and evangelical groups. According to the traditional archetypes of femininity, these groups espouse values and moral rules on the family, impacting on the beliefs and expectations of gender and dating relationships, as well as promoting the tolerance of violence ( Alcaino, 2017 ; Berkel et al, 2004 ; Betancourt & Cartes, 2019 ; Jankowski et al, 2018 ; King & Boyatzis, 2015 ; Nelson, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Chile, Christian spirituality is strong, because most of the population identifies with Catholic and evangelical groups. According to the traditional archetypes of femininity, these groups espouse values and moral rules on the family, impacting on the beliefs and expectations of gender and dating relationships, as well as promoting the tolerance of violence ( Alcaino, 2017 ; Berkel et al, 2004 ; Betancourt & Cartes, 2019 ; Jankowski et al, 2018 ; King & Boyatzis, 2015 ; Nelson, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on religion and social status has suggested that religious preferences in stratified societies can in many cases be conceived of as forms of cultural consumption (Sherkat and Wilson 1995;Alcaino and Mackenna 2017) which, similar to other forms of consumption, speaks of people´s position in social space (see Lindhardt 2012;Koehrsen 2016Koehrsen , 2017. In a study of Argentine Pentecostalism, the Swiss sociologist Jens Koehrsen adopts a Bourdieuan perspective as he shows how middle-class Pentecostals have developed particular expressive styles such as calm services and a verbal, intellectual practice of religion, that distinguish them from more popular and emotional expressions of Pentecostalism (Koehrsen 2016(Koehrsen , 2017.…”
Section: Turning Pentecostalism On the Ground Into A Legitimate Religionmentioning
confidence: 99%
“…Consistent with this claim, educational mobility continues to influence religious switching, especially to mainline Protestantism (Schwadel 2011). Recent work, however, finds that educational attainment is less determinative of religious switching in recent cohorts (Scheitle and Smith 2012), though increasing intergenerational mobility of conservative Protestants may drive religious switching (Everton 2005) and cross-national variation in the relation of socioeconomic status and switching must be considered (Alcaino and Mackenna 2017; Doebler and Shuttleworth 2018; Haskell, Burgoyne and Flatt 2016).…”
Section: Literature Reviewmentioning
confidence: 99%